Out-of-hospital cardiac arrest: assessing the problem status and identifying priority areas for improving the care provision. Data from the 2020-2022 Crimean registry - A. A. Birkun; L. P. Frolova; G. N. Buglak (Российский кардиологический журнал, 2024)
Aim. To study the regional epidemiological characteristics of out-of-hospital cardiac arrest (OHCA), the process and effectiveness of care for OHCA, and identify priority areas for improving the care provision.Material and methods. An analysis of the data from the "Crimean registry of cases of OHCA and cardiopulmonary resuscitation" was performed. The study used data from 2020 to 2022. The analytical sample consisted of all OHCA cases developed before the ambulance arrival, followed by cardiopulmonary resuscitation (CPR).Results. Of the 356 OHCA cases occurred before the ambulance arrival, followed by CPR (2020 — 141, 2021 — 103, 2022 — 112), in 65,2% of cases (n=232) cardiac arrest developed in men, in 64,0% (n=228) — in city residents, 70,2% (n=250) — in private houses or apartments. The mean age was 59 years (median 62 years). The cause of 89,6% of OHCA cases (n=319) was disease, 3,9% (n=14) — drowning, 2,8% (n=10) — trauma, 2,0% (n=7) — asphyxia, 1,1% (n=4) — toxicity, 0,6% (n=2) — electrical injury. In addition, 7,3% (n=26) of patients survived. Bystanders attempted CPR before ambulance arrived in 27,2% (n=97) of cases. In cases where CPR was performed by bystanders, ambulance specialists were 2,5 times more likely to register a potentially shockable rhythm on the primary electrocardiogram (19,6% and 7,7%, respectively; p=0,001), 2,2 times more often performed defibrillation (22,7% and 10,4%, respectively; p=0,003). When defibrillation was performed, the proportion of survivors was 3,9 times higher than without defibrillation (20,4% and 5,2%, respectively; p=0,001).Conclusion. Conducting CPR by OHCA bystanders increases the success rate of CPR performed by ambulance team. However, bystanders rarely provide first aid, which causes a high mortality rate. To reduce mortality in OHCA, the attention should be focused on the development, implementation and regulatory support of measures aimed at involving the population in providing first aid. This should include regular population training in CPR, widespread popularization of first aid, remote provision of CPR instructions by emergency dispatchers to untrained OHCA bystanders and ensuring the availability of automated external defibrillators.